M.E.S.H. for mechanical engineers - Sršníková, Daniela; Stančeková, Dana (University of Žilina : EDIS-Publishing House UNIZA, 2025)
This coursebook has been designed to help students improve both their receptive and productive language skills, empowering them to combine their engineering knowledge with linguistic competence to present complex engineering concepts confidently in English